2012
DOI: 10.1021/om3002747
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Bound Trifluoromethoxide Complexes of Copper and Gold

Abstract: Well-defined copper and gold complexes have been prepared which contain the shortest structurally characterized metal−oxygen bonds between transition metals and a trifluoromethoxide moiety. The trifluoromethoxide ligand is O-bound to both the copper and gold centers, with a copper−oxygen distance of 1.849(4) Å and a gold−oxygen distance of 2.058(4) Å. Density functional theory (DFT) calculations on all new trifluoromethoxy complexes were performed in order to obtain bond lengths and angles that are not influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 20 publications
(45 reference statements)
2
62
0
8
Order By: Relevance
“…We next turned our attention to identify a ligand to stabilize difluoromethylated coinage metal complexes. Because strong s-donating N-heterocyclic carbenes (NHCs) have successfully been employed in stabilizing many coinage metal complexes [37][38][39][40][41][42] , we sought to determine if NHC ligands could stabilize AgCF 2 H that was known to undergo homolytic cleavage of Ag-C(CF 2 H) bond to form HCF 2 and Ag(0) even at À 50°C. It was found that NHCligated difluoromethyl-silver complex [(SIPr)Ag(CF 2 H)] (SIPr: 1,3-bis(2,6-diisopropyl phenyl) imidazolin-2-ylidene) 6 could be prepared in 82% yield by the reaction of [(SIPr)AgCl] with 2.0 equivalents of TMSCF 2 H in THF at room temperature in the presence of 2.0 equivalents of NaO t Bu (Fig.…”
Section: )] (Ref 36)mentioning
confidence: 99%
“…We next turned our attention to identify a ligand to stabilize difluoromethylated coinage metal complexes. Because strong s-donating N-heterocyclic carbenes (NHCs) have successfully been employed in stabilizing many coinage metal complexes [37][38][39][40][41][42] , we sought to determine if NHC ligands could stabilize AgCF 2 H that was known to undergo homolytic cleavage of Ag-C(CF 2 H) bond to form HCF 2 and Ag(0) even at À 50°C. It was found that NHCligated difluoromethyl-silver complex [(SIPr)Ag(CF 2 H)] (SIPr: 1,3-bis(2,6-diisopropyl phenyl) imidazolin-2-ylidene) 6 could be prepared in 82% yield by the reaction of [(SIPr)AgCl] with 2.0 equivalents of TMSCF 2 H in THF at room temperature in the presence of 2.0 equivalents of NaO t Bu (Fig.…”
Section: )] (Ref 36)mentioning
confidence: 99%
“…The two Ag−N bonds are substantially different [Ag(trifluoromethoxide ligand is significantly shorter than that of the Ag(1)−O(THF) (2.502(4) Å), but is significantly longer than that found in the related complexes (SIPr)MOCF 3 (M = Cu: 1.849(5) Å; M = Au: 2.058(4) Å). 40 Moreover, the M−O(1)−C(1) (M = Ag) angle in 1 is 125.3(3)°, which is larger than those found in (SIPr)MOCF 3 (M = Cu: 120.7(5)°; M = Au: 123.3(7)°) 40. …”
mentioning
confidence: 91%
“…11,16,17 This is due to (i) strong electron repulsion between three fluorine atoms and an incoming nucleophile; (ii) formation of energetically disfavoured CF 3 carbocation transition state structure (TS); and (iii) competing iodination of nucleophiles due to the reversed electron density. In addition, the thermal instability of transition metal–OCF 3 complexes (they readily decompose to form fluorophosgene and metal fluoride) 18 and the poor nucleophilicity of the OCF 3 anion (a reactive electrophile is needed for the C–OCF 3 bond formation) 19 have hampered the development of the C–OCF 3 bond formation through either transition metal-catalysed C–O bond formation or nucleophilic substitution. Strategies for the synthesis of trifluoromethoxylated heteroaromatic compounds are very rare.…”
Section: Introductionmentioning
confidence: 99%